Gene Expression with General Purpose Graph Rewriting Systems - Schimmel, Jochen; Gelhausen, Tom; Schaefer, Christoph (Electronic Communications of the EASST, 2009)
We show that a general purpose graph rewriting system (GRS) nowadays is capable of simulating gene expression, the intra-cellular synthesis of proteins. The model organism we use is one of the best-studied prokaryotic life-forms in genetics, the E. coli bacteria. Our graph representation of the E. coli DNA consists of 23 Million graph elements. In our case study we correctly synthesize the proteins of 30 consecutive genes. In this paper we describe our approach as well as our observations. Further on, we discuss some potential extensions to GRSs that would support more sophisticated simulations.